Gutta Percha Sebagai Bahan Pengisian pada Perawatan Endodontik Pasien Celah Langit-langit - Sekar Pratiwi; Yetty Herdiyati (Jurnal Material Kedokteran Gigi, 2018)
Comprehensive care is needed in patients with cleft lip and palate. Treatments to be performed on patients include corrective surgery and orthodontic treatment. One of the treatments that should be prepared before corrective surgery is the rehabilitation of the oral cavity. A girl aged 15 years came to the Cleft Center RSGM FKG Unpad to get treatment for her cleft palate. The treatment plan will include pre-bone grafting orthodontic treatment, bone grafting, and the post-bone grafting orthodontic treatment. In preparation for that, rehabilitation of the oral cavity need to be done, including root canal treatment for teeth 11, 26 and 46 that was diagnosed with necrotic pulp, and composite restorations to tooth 25. Treatment is done with manual ProTaper system (hand-use) and the filler selected was gutta-percha because the success rate is high. Root canal treatment on the tooth 11, 26, 46 has been done and achieved the expected results. The patient is now on the stage of pre bone grafting orthondontic treatment. Gutta-percha is an option for root canal filling material, made from natural materials, flexible, and adequate in filling root canals together with sealer, and more stable to degradation. One of the keys to success for correction of cleft lip and palate is the free-infection oral environment that were achieved during the rehabilitation of the oral cavity due to support further treatment stage.